KOMPETENSI PEDAGOGIK GURU PENDIDIKAN KEWARGANEGARAAN DALAM MEMBANGUN KECERDASAN BERDEMOKRASI WARGA NEGARA - Rohmawati, Rini; ., Triyanto; Muchtarom, Moh. (PKn Progresif, 2016)
The objectives of research were: 1) to describe the pedagogic competency of civic education?s teacher in building democratic intelligence among the 8th Graders of SMP Negeri 1 Kebakkramat, 2) to explain the factors supporting and inhibiting the Civic Education teacher in building democratic intelligence, and 3) to find out the effect of Civic Education teacher?s pedagogic competency in building democratic intelligence of the 8th Graders of SMP Negeri 1 Kebakkramat. This research employed a qualitative research. Considering the result of research, the following conclusions could be drawn. 1) Civic Education teacher?s pedagogic competency in building democratic intelligence was implemented through teaching-learning activity inside and outside classroom. Teacher?s pedagogic competency included understanding on students, designing the learning, implementing the learning, evaluating the learning and developing the students? potency. 2) The factors supporting Civic Education teacher?s pedagogic competency included school mission, learning time allocation, activity implemented by school, complete learning facility, teacher?s pedagogic competency, and student ability. Meanwhile, the inhibiting factors included: a) internal factors: students were still crowded in learning time and teacher sometimes focused only on transfer of knowledge, b) external factor: family environment and peer?s effect. 4) The effect of Civic Education teacher?s competency included: a) tolerance, respect and appreciating diversity, b) questioning and expressing opinion bravely, c) maintaining togetherness, and d) participating actively.